The Effect of Changes in Tax Rate, Profitability, Liquidity, and Corporate Governance to Management Profit on Manufacture Industry - Septyana Prasetianingrum; Yaya Sonjaya; Laode Marihi; Entar Sutisman; Sahrul Ponto (Golden Ratio of Taxation Studies, 2021)
Study this aim for analyze influence Change Rates Tax PPH Body year 2008, Profitability, Liquidity, and Corporate Governance of Management in the annual reports of industrial companies Manufacture in Indonesia. Study this expected could give contribution in knowledge accountancy and theory development especially with regard to corporate earnings management practices in annual reports company. Type study this is study quantitative with analysis data use regression linear double with the SPSS program. The research sample is 8 manufacturing industry companies listed on the Stock Exchange Indonesia and data which used is data secondary form report finance period 2006-2010. Results this study states that the measure of liquidity positive and significant effect, while the measure of change The 2008 Corporate PPH Tax Rate, Profitability, and Corporate Governance have an effect on Profit Management negative to management profit.